POSITIVE REINFORCEMENT APPLICATION TO IMPROVE STUDENT LEARNING MOTIVATION - Karomah, Siti; Purwati, Purwati; Sugiyadi, Sugiyadi (Universitas Muhammadiyah Magelang, 2014)
This study aimed to test whether or not the application of positive reinforcement to increase students? motivation. This research was conducted at class VIII MTs Walisongo Sidowangi Kajoran 3. This research using action research methods Guidance and Counseling (PTBK). The subjects of this study were three children who had low levels of motivation in learning. Data collection method used is the method of observation and interviews. The data obtained were analyzed by constant percentage analysis techniques. The results showed that there was a change in the students? motivation after application of positive reinforcement. This i evidenced by the increase in student motivation. In addition, increase the frequency of indicators that show the percentage of more than 50% in accordance with the target date. Increasing student motivation is characterized by students who initially did not want to do the tasks assigned by the teacher be willing to do, which was originally often rowdy students in the classroom to be reduced, and the concentration of students become more willing to listen to the explanation given by the teacher.